CONCRETE CRACK-FORMATION MODELING UNDER ACTION OF CORRODING REINFORCEMENT - S. N. Leonovich (Наука и техника)
Physical and numerical models of cracks are proposed for analysis of their formation and development which are based on the main assumption that there is a сut of circular shape in the place of the rusty bar and its contour is subjected to a pressure initiated by rust pressure.